The Effectiveness of Chamomile Aromatherapy on Sleep Quality in Infants Aged 6-8 Months at the Tosa Community Health Center, Tidore Islands City - Putri Ayu Ibrahim; Anik Purwati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Sleep disturbances in infants aged 6–8 months are a common problem encountered in midwifery practice and pediatric healthcare, and can impact infant growth, neurological development, and emotional balance. Midwives play a crucial role in providing education and safe, non-pharmacological methods to enhance the quality of a baby's sleep. Chamomile aromatherapy, which has a slight sedative and soothing effect, is one possible additional treatment. The purpose of this study was to examine how well infants at the Tosa Community Health Center in Tidore Islands City, ages 6 to 8 months, slept after receiving chamomile aromatherapy. The study employed a pretest–posttest control group methodology in a quasi-experimental design. For seven days in a row, the intervention group used a diffuser to provide chamomile aromatherapy 20 minutes before bed, while the control group did not receive any intervention. The Brief Infant Sleep Questionnaire (BISQ), which measures sleep length at night, frequency of awakenings, total sleep duration, and effective sleep, was used to assess the quality of infant sleep. The intervention group significantly outperformed the control group on every measure of sleep quality (p < 0.05). In newborns between the ages of six and eight months, chamomile aromatherapy has been demonstrated to be beneficial in improving the length and quality of sleep as well as decreasing the number of awakenings. This intervention can be recommended as part of complementary midwifery care in promotive and preventive efforts to improve the quality of infant growth and development in primary healthcare settings.